A Mobile Agent–Based Method for Logistics Coordination Management - Chen, Yong (International Journal of Interactive Mobile Technologies (iJIM), 2026)
To address the fundamental limitations of conventional logistics coordination systems— including delayed responses in dynamic environments, low collaboration efficiency, and rigid resource allocation—a cloud–edge–end collaborative mobile agent management framework for logistics scenarios was proposed by integrating recent advances in mobile agents, mobile edge computing, and digital twin technologies. This study introduced three major technical innovations. At the architectural level, a digital twin–driven, hierarchically decoupled open ecosystem was constructed, overcoming the constraints of traditional centralized control paradigms. At the mechanism level, a multimodal coordination mechanism was designed, achieving dynamic multi-issue task allocation, supporting context-aware adaptive decision-making, and enhancing the handling of complex problems. At the technical level, mobile edge computingenabled task offloading strategies and lightweight real-time digital twin simulation were integrated to improve real-time responsiveness and reduce device energy consumption in mobile environments. To validate the effectiveness of the proposed framework, two representative experimental scenarios were constructed: a warehouse–distribution integrated automated guided vehicle coordination scenario and an urban last-mile hybrid delivery scenario involving unmanned aerial vehicles and automated guided vehicles. Comparative simulation experiments were conducted using an AnyLogic–ROS co-simulation platform. The results demonstrate that the proposed method significantly outperformed conventional centralized scheduling and standard multi-agent approaches in terms of end-to-end decision latency, task conflict resolution success rate, energy consumption, and adaptability to dynamic environments. These findings provide an innovative paradigm and robust technical support for the large-scale application of mobile agent technologies in logistics coordination management.